Auditory Brainstem Response (ABR) modulation as an alternative method to measure sensory gating. - Sulaiman, Nur Hafizah; Dzulkarnain, Ahmad Aidil Arafat; Maamor, Nashrah; Rahmat, Sarah (2021)
Introduction: Electroencephalogram (EEG) through event-related potential (ERP) of P50 has been widely used to measure sensory gating. However, this method of assessment is not always available. Considering the importance of sensory gating, this study aimed to investigate the potential use of ABR test with Stroop Task as an alternative method to objectively measure sensory gating, particularly among APD children.